Comparison of the composition of lymphocyte subpopulations in non-relapse and relapse patients with squamous cell carcinoma of the head and neck before, during radiochemotherapy and in the follow-up period: a multicenter prospective study of the German Cancer Consortium Radiation Oncology Group (DKTK-ROG) - Niu, Minli; Combs, Stephanie; Linge, Annett; Krause, Mechthild; Baumann, Michael; Lohaus, Fabian; Ebert, Nadja; Tinhofer, Ingeborg; Budach, Volker; Müller-von der Grün, Jens; Rödel, Franz; Grosu, Anca-Ligia; et al. (Radiation oncology, 2021)
Radiochemotherapy (RCT) has been shown to induce changes in immune cell homeostasis which might affect antitumor immune responses. In the present study, we aimed to compare the composition and kinetics of major lymphocyte subsets in the periphery of patients with non-locoregional recurrent (n = 23) and locoregional recurrent (n = 9) squamous cell carcinoma of the head and neck (SCCHN) upon primary RCT.